Reactivity, stability, and thermodynamics of para-methylpyridinium-based ionic liquids: Insight from DFT, NCI, and QTAIM - Ededet A. Eno; Hitler Louis; Tomsmith O. Unimuke; Terkumbur E. Gber; Idongesit J. Mbonu; Chinwendu J. Ndubisi; Stephen A. Adalikwu (Journal of Ionic Liquids, 2022)
Ionic liquids (ILs) have lately piqued scientific attention due to their potential applications in green transition technologies such as catalysis, electrochemistry, and photovoltaic. The investigation of structural stability, reactivity, topological analysis, and thermodynamics of 4-methylpridine (4-picoline) based ILs is carried out using an advanced computational electronic structure theory technique based on first principle density functional theory (DFT). The ILs were modeled based on the interaction of 4-methylpridine (4-picoline) ion (cation) with borate, nitrate, phosphate, carbonate, and sulfate anions which have been chemically symbolized respectively as follows: [PMHP]+[HBO3]−, [PMHP]+[HNO3]−, [PMPH]+[HPO3]−, [PHMP]+[HCO3]−, and [PHMPM]+[HSO4]−. The energy difference between HOMO - LUMO of the studied compounds were found to show a general decreasing trend in the order: [PMHP][H2BO3] > [PMHP][NO3]> [PMPH][H2PO3]> [PHMP][HCO3]> [PHMPM][HSO4] with the borate ([PMHP][H2BO3]) and sulfate ([PHMPM][HSO4]) ILs having the relatively highest and least energy gap of 6.30 and 4.14 eV respectively. Strong interaction energies of 329.50 kca/mol, 114.41 kcal/mol, 107.12 kcal/mol, 98.19 kcal/mol and 87.86 kcal/mol involving the bonding, anti – bonding and lone pair orbitals associated with the pair of ILs were obtained as a trend: [PMHP][HSO4] > [PMHP][HCO3] > [PMPH][H2BO3] > [PHMP][NO3] > [PHMPM][H2PO3]. The intermolecular hydrogen bond (H-bond) analysis between the cation and anions ILs pairs obtained from quantum theory of atoms-in-molecules (QTAIM) reveals strong, weak, and electrostatic bonds. [PMPH]+[HSO4]− ILs pair was observed to possess the highest binding energy of -20.06 kcal/mol in the same way energy decomposition analysis (EDA) reveals a relatively strong orbital interaction in the [PMPH][HSO4] ILs due to the increase in electrostatic interaction of the four O-atoms in the sulfate anion, the analysis of the thermodynamic results indicates that the syntheses of the ILs are exothermic and spontaneous.